High-precision measurement of plasmonic phase change in metal nanostructures - Nguyen, Duy Anh (Nanyang Technological University, 2020)
The plasmonic phenomenon of Extraordinary Optical Transmission (EOT) refers to the interaction of the light and a metallic film perforated with the subwavelength holes. It provides a larger transmission of electromagnetic fields than the transmission predicted from a small aperture by the classical optics. Many of the initial research works on this topic have focused on studying the intensity behavior (the transmittance) on all the sample parameters such as hole size, periodicity, thickness, type of metal, and the shape of the hole. The phase behavior has, to date, not been much explored although it is an inherent and important feature for plasmonic processes because of the critical requirements for highly stabilized light sources, coherent optical interferometers, and stable optical paths that are impervious to environmental changes. Therefore, this thesis has investigated the ability of the two interferometric approaches to measuring the plasmonic EOT phase, which are named as frequency comb referenced (FCR) plasmonic phase spectroscopy. Frequency comb transfers the phase information in the optical domain to the radio-frequency domain, thereby enable broadband plasmonic phase spectroscopy to have a higher speed, higher precision, and direct traceability to the time standards. The strong confinement of surface plasmons at metal surfaces makes them highly sensitive to the nanoscale structural shapes and local refractive index changes induced by biomolecular surface binding, molecular composition changes. As an example, a 1.94 Å dynamic motion of a pair of nanoholes was measured with a 1.67 pm resolution in the feasibility test experiment, which shows the ability of plasmonic phase spectroscopy to function as a high-precision plasmonic ruler. In the refractive index measurement, the FCR-plasmonic phase spectroscopy successfully measured the gas refractive index change Δn = 4.6 × 10-9 RIU with the resolution of δn = 1.6 × 10-11 RIU. With this superior performance, the FCR plasmonic phase spectroscopy has a lot of potentials to be applied to various applications such as bio-molecular detection, plasmonic ruler, and precision calibration of nano-instruments.